Taiwan`s domestic politics since the presidential elections 2000 - Hermann Halbeisen (University of Duisburg-Essen, Institute of East Asian Studies (IN-EAST), 2003)
This paper looks at several developments that have taken place in domestic politics on Taiwan since the election of Chen Shui-bian as president of the Republic of China on Taiwan in 1998. After discussing the political successes and failures of the incumbent Chen administration, it analyses its strategy in dealing with the consequences of divided government. Some of the problems encountered by the administration are traced to changes in the political system of Taiwan that took place during the presidency of Lee Teng-hui. The paper also deals with the new role of the president as chief executive and functioning of the legislative. Finally, the reaction of the major political parties to the changes in the political situation is explored.
Keywords: 320; Taiwan; domestic politics; divided government; political system; party system; Chen Shui-bian; Lee Teng-hui